The Effect of Ease of Use, Service Features, Benefits, Trust, Security, and Risk on Interest in Using LINKAJA SYARI'AH E-Wallet - Lafiana, Diah; Purnomo, Agus; Al Hadi, M. Qoshid Al Hadi; Hadi, Abdul; Hani, Umi (Assyarikah: Journal of Islamic Economic Business, 2025)
This study aims to determine the effect of ease of use, service features, usefulness, trust, and risk on the interest in using the LinkAja Syariah e-wallet in Banjarmasin City. This study uses a quantitative research method. By using purposive sampling from E-Wallet transaction users in responding to challenges in digital economic transactions. The sampling method uses a purposive sampling technique. So that a sample of 100 respondents was obtained. Analysis of the data obtained using hypothesis analysis to determine the effect of ease of use, service features, usefulness, trust, security, and risk on E-Wallet service features. Based on the research results 1) ease of use (X1) does not have a significant effect on the interest in using the LinkAja Syariah e-wallet, obtaining a sig. value of 0.368>0.05. 2) service features (X2) have a significant effect on the interest in using the LinkAja Syariah e-wallet by obtaining a sig. value of 0.024<0.05. 3) usefulness (X3) does not have a significant effect on the interest in using the LinkAja Syariah e-wallet, obtaining a sig. value of 0.107>0.05. 4) trust (X4) does not have a significant effect on the interest in using the LinkAja Syariah e-wallet, obtaining a sig. value of 0.710>0.05. 5) security (X5) has a significant effect on the interest in using the LinkAja Syariah e-wallet by obtaining a sig. value of 0.000<0.05. and 6) Risk (X6) has no significant influence on the interest in using the LinkAja Syariah e-wallet by obtaining a sig. value of 0.372>0.05. The findings of this study show that E-wallet transactions play a very important role in meeting community needs.